2015
DOI: 10.1007/s00441-015-2257-x
|View full text |Cite
|
Sign up to set email alerts
|

Some assembly required: evolutionary and systems perspectives on the mammalian reproductive system

Abstract: In this review, we discuss the way that insights from evolutionary theory and systems biology shed light on form and function in mammalian reproductive systems. In the first part of the review, we contrast the rapid evolution seen in some reproductive genes with the generally conservative nature of development. We discuss directional selection and coevolution as potential drivers of rapid evolution in sperm and egg proteins. Such rapid change is very different from the highly conservative nature of later embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 160 publications
(180 reference statements)
0
5
1
Order By: Relevance
“…Overall, our findings of sequence conservation over such long evolutionary time periods are contrary to observations within many other organisms, where elevated signals of positive selection are detected in seminal fluid proteins [ 33 35 ]. From an evolutionary perspective, then, patterns of evolution in secreted membranous organelle proteins do not match expectations for typical seminal fluid proteins.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, our findings of sequence conservation over such long evolutionary time periods are contrary to observations within many other organisms, where elevated signals of positive selection are detected in seminal fluid proteins [ 33 35 ]. From an evolutionary perspective, then, patterns of evolution in secreted membranous organelle proteins do not match expectations for typical seminal fluid proteins.…”
Section: Discussioncontrasting
confidence: 99%
“…additionally highlight fascinating observations that aspects of the latter are conserved across the kingdoms of life [22], and that the Crabtree and Warburg effects of yeast and cancer cells, respectively, harbor considerable metabolic similarities [75,76], suggesting that the drive for efficient functionality means that convergent evolution has an amazingly broad scope. Staying at the general level, a recent modeling study evaluated E. coli metabolism with regard to what the authors refer to as 'diversity-generating biosynthesis', which they postulate evolved to produce large numbers of different metabolites [77].…”
Section: The Evolution Of Plant Metabolic Diversitymentioning
confidence: 88%
“…However, the dynamics of the latter case are predominantly driven by molecular interactions, as opposed to behavioral ones, and therefore the appropriate unit of evolutionary analysis is the molecular evolution of the reproductive proteome ( McDonough et al 2016 ; Wilburn and Swanson 2016 ). Studies across a wide range of vertebrate and invertebrate taxa have consistently shown that reproductive proteins have an elevated ratio of nonsynonymous to synonymous substitutions relative to nonreproductive proteins ( Swanson and Vacquier 2002 ; Clark et al 2006 ; Vacquier and Swanson 2011 ; Mordhorst et al 2015 ). In fact, sperm-specific, seminal fluid, and egg-specific proteins evolve at astonishingly rapid rates, and are often the fastest observed within a given genome.…”
mentioning
confidence: 99%